The use of lignocellulosic byproducts and cellulose nanocrystals within particleboard production - Mesquita, Ricardo Gabriel de Almeida (2017)
The objective of this work was to study the particleboard production using Eucalyptus particles, sisal filaments, coconut filaments (coir) and sugarcane bagasse particles (SCB). All particleboards were made in three layers (face / core / face) using urea-formaldehyde adhesive (UF). Coir and sisal filaments were used in association with Eucalyptus particles, only in the inner layer (core), in proportions of 0, 10 and 20%. The SCB particles were separated into pith and fibers and the particleboards were made using only fibers and using fibers on the faces and pith in the core. SCB particleboards were also manufactured using 1% of cellulose nanocrystals (NCC), by adhesive mass, on the faces of the particleboards. The proportion of NCC was defined using urea-formaldehyde specimens, reinforced with different proportions of NCC (0, 0.5, 1, 2, 3 and 5%). For the particleboards production, a pressing cycle was used with the following characteristics: temperature of 160°C, pressure of 4 MPa and time of 8 minutes. The properties evaluated were: water absorption (WA), thickness swelling (TS), density, compaction ratio, modulus of elasticity (MOE), modulus of rupture (MOR), internal bond (IB) and thermal conductivity (TC). The particleboards reinforced with sisal did not show satisfactory results for most of the properties evaluated (MOE, MOR, WA, IB and TC), but those reinforced with coconut, showed properties very similar to the particleboards made only with Eucalyptus particles, demonstrating the potential of this material. The filaments of sisal formed tufts that impaired the dispersion of the adhesive inside the tufts, reflecting in poor physical-mechanical properties. The specimens of UF reinforced with NCC (1, 2 and 3%) presented higher results (MOE and MOR) than non-reinforced specimens did, but the same was not observed when the NCC were applied in the SCB particleboards. NCC were probably able to bind with the adhesive, decreasing the amount of sites for the bonds between the adhesive and SCB particles. Particleboards made with fibers and fibers/pith showed properties statistically equal for most properties (MOE, MOR, WA and TC). SCB showed potential for MDP production.